Modified support phase appliance after twin block therapy - Gautham Sivamurthy; S Aravind Kumar; Christine Samantha (Wolters Kluwer Medknow Publications, 2014)
Buccal segment occlusion is the cornerstone of stability after correction of Class II malocclusion using a twin block appliance. The following short communication is a modification of Clark's original support phase appliance, to achieve better retention after treatment.